Male-female concordance in reported involvement of women in contraceptive decision-making and its association with modern contraceptive use among couples in rural Maharashtra, India - Anvita Dixit; Nicole E. Johns; Mohan Ghule; Madhusudana Battala; Shahina Begum; Jennifer Yore; Niranjan Saggurti; Jay G. Silverman; Elizabeth Reed; Tarik Benmarhnia; Sarah Averbach; Anita Raj (BMC, 2021)
Plain language summary Evidence on women's involvement in decision-making are limited to women's self reports and often not specific to contraceptive decision-making. This study uses couples dyadic data to assess male-female concordance on women's involvement in contraceptive decision-making and contraceptive use outcomes. Couple's concordance on women's involvement in contraceptive decision-making is associated with contraceptive use. There is potential in couple-focused family planning counseling that enhances women's contraceptive decision-making agency to improve women's contraceptive use.